The Effect of PayLater Usage on Financial Well-Being: The Moderating Roles of Financial Anxiety and Self-Control among Young Consumers - Chairul Suhendra; A. Rozi (Al-Masraf : Jurnal Lembaga Keuangan dan Perbankan, 2026)
This study aims to examine the effect of PayLater usage on financial well-being and investigate the moderating roles of financial anxiety and self-control among young consumers in Bengkulu. A quantitative explanatory approach with a cross-sectional design was employed. Data were collected through a structured questionnaire administered to young consumers selected via purposive sampling and analyzed using Moderated Structural Equation Modeling based on Partial Least Squares. The findings demonstrate that PayLater usage has a direct adverse effect on financial well-being. Financial anxiety exacerbates this negative relationship, rendering consumers with higher anxiety more vulnerable to declining financial security. Conversely, self-control serves as a protective psychological mechanism that mitigates the detrimental impact of PayLater usage on financial well-being. The proposed model offers substantial explanatory capability in understanding consumer financial well-being. These findings underscore the importance of responsible credit limits, transparent repayment information, enhanced consumer self-regulation, and targeted digital financial education that addresses installment planning and financial anxiety management.